The effect of products from bronchoalveolar-derived neutrophils on oxidant production and phagocytic activity of alveolar macrophages. - Donaldson, K (1988)
Neutrophils and alveolar macrophages are found together in the alveolar region during pulmonary inflammation where neutrophil products could influence important macrophage defensive functions. We set out therefore to investigate the ability of neutrophil products to modulate alveolar macrophage phagocytosis and oxidant production. Neutrophils derived from acutely inflamed rat lung were incubated along with a range of potential triggers of neutrophil secretion and supernatants collected. Using two quantitative assays of rat alveolar macrophage phagocytosis, the supernatants were found to have no effect except for the quartz supernatant, which slightly enhanced phagocytosis via non-specific receptors and the PMA supernatant, which caused reduction in phagocytosis via non-specific and Fc receptors; this reduction could however be mimicked by PMA alone. None of the supernatants affected macrophage production of superoxide anion or hydrogen peroxide except for the PMA supernatant and once again the inhibitory effect of the PMA supernatant could be mimicked with PMA alone. It is concluded that products of inflammatory neutrophils do not affect phagocytosis or oxidative metabolism of alveolar macrophages, although in quartz-exposed lung neutrophils may exert a small enhancing effect on macrophage phagocytosis.